The effect of an additional pre-extubational loading dose of caffeine citrate on mechanically ventilated preterm infants (NEOKOFF trial): Study protocol for a multicenter randomized clinical trial - Kinga Kovács; Rita Nagy; Lilla Andréka; Brigitta Teutsch; Miklós Szabó; Péter Varga; Péter Hegyi; Péter Hársfalvi; Nándor Ács; Ágnes Harmath; Csaba Nádor; Ákos Gasparics (PLoS ONE, 2025)
Background Minimizing the duration of mechanical ventilation is one of the most important therapeutic goals during the care of preterm infants at neonatal intensive care units (NICUs). The rate of extubation failure among preterm infants is between 16% and 40% worldwide. Numerous studies have been conducted on the assessment of extubation suitability, the optimal choice of respiratory support around extubation, and the effectiveness of medical interventions. Since the Caffeine Therapy for Apnea of Prematurity (CAP) trial, caffeine has become one of the essential drugs at NICUs. However, the optimal dosage and timing for adequate effectiveness still need to be more conclusive. Previous studies suggest that higher doses of caffeine treatment increase the success rate of extubation. Therefore, we aim to determine whether using a single additional loading dose of caffeine citrate one hour prior to extubation impacts the success rate of extubation. Methods The study is an open-label, multicenter randomized clinical trial testing the effectiveness and safety of pre-extubational loading dose of caffeine citrate. Inclusion criteria will be infants born before the 32nd gestational week, before the first extubation attempt after at least 48 hours of mechanical ventilation, and a signed parental informed consent. A total of 226 patients will be randomly allocated to either the experimental or control group. The randomization will be stratified by gestational age and antenatal steroid prophylaxis. Preterm infants in the experimental group will receive an additional intravenous (IV) loading dose (20 mg/kg) of caffeine citrate one hour before the first planned extubation, in addition to the standard dosing regimen (20 mg/kg caffeine citrate IV on the first day of life and 5 to 10 mg/kg IV or orally caffeine citrate each consecutive day). Preterm infants in the control group will receive the standard dosing regimen. The primary outcome will be reintubation within 48 hours. Discussion A pre-extubational loading dose of caffeine citrate can reduce extubation failure. Obtaining evidence on this feature has the potential to contribute to finding the optimal dosing regimen. Trial registration number The study protocol was approved by the Hungarian Ethics Committee for Clinical Pharmacology of the Medical Research Council and National Institute of Pharmacy and Nutrition (OGYÉI/6838-11/2023). ClinicalTrials.gov identifier NCT06401083 Registered 06. May 2024.; EudraCT number: 2022-003202-77.